FracFeed : Global database of the fraction of feeding predators - Mark Novak; Paige Foust; Shannon Hennessey; Brian P. Tanis; Kyle E. Coblentz; Christopher Wolf; Leah M. Segui; Jeremy S. Henderson; Kurt E. Ingeman; Landon P. Falke; Tamara J. Layden; Daniel J. Gradison; et al. (Ecology, 2026)
The proportion of individuals that are found to have empty stomachs during a survey of a predator population's diet has been used as an indicator of the average individual's state of energy balance and of the degree to which its feeding rate (i.e., its functional response) is saturated with respect to prey availability. As such, the proportion of empty stomachs provides insights into the effects of prey on predators and vice versa, although it is typically unreported in deference to descriptions of the contents of the non‐empty stomachs. The FracFeed database is an ongoing compilation of the proportions of empty and non‐empty stomachs (for gut content surveys) and of feeding and not feeding individuals (for direct observation surveys) reported in publications of predator diet surveys. FracFeed contains data from 4920 diet surveys on 1507 taxa (>4.3 million individuals) spanning cnidarians, ctenophores, chaetognaths, birds, annelids, amphibians, arthropods, mammals, mollusks, reptiles, echinoderms, and fishes that were surveyed in terrestrial, marine, and freshwater ecosystems across the globe over more than 135 years (1887–2023). For most surveys, covariate data include information on the spatial and temporal extent of the diet survey, its central geographical coordinates, the method by which the survey was performed (lethal gut contents, lavage, or direct observation), as well as each predator's standardized taxonomic name and identifier in the Open Tree of Life, its body mass (compiled mostly from independent compilations and additional publications), and its apparent diet's taxonomic richness and resolution. We appeal to more researchers who perform diet surveys to report on the number of empty stomachs they find and encourage additional contributions to the database—particularly from underrepresented geographic regions (e.g., North and Central Asia, North and Central Africa)—to help grow its scope and utility. The database is provided under a CC‐BY‐NC‐S4 4.0 license. Users are requested to cite this data paper when using the data.

Predicting Cognitive Functioning for Patients with a High-Grade Glioma: Evaluating Different Representations of Tumor Location in a Common Space - S. M. Boelders; W. De Baene; E. Postma; K. Gehring; L. L. Ong (Neuroinformatics, 2024)
Cognitive functioning is increasingly considered when making treatment decisions for patients with a brain tumor in view of a personalized onco-functional balance. Ideally, one can predict cognitive functioning of individual patients to make treatment decisions considering this balance. To make accurate predictions, an informative representation of tumor location is pivotal, yet comparisons of representations are lacking. Therefore, this study compares brain atlases and principal component analysis (PCA) to represent voxel-wise tumor location. Pre-operative cognitive functioning was predicted for 246 patients with a high-grade glioma across eight cognitive tests while using different representations of voxel-wise tumor location as predictors. Voxel-wise tumor location was represented using 13 different frequently-used population average atlases, 13 randomly generated atlases, and 13 representations based on PCA. ElasticNet predictions were compared between representations and against a model solely using tumor volume. Preoperative cognitive functioning could only partly be predicted from tumor location. Performances of different representations were largely similar. Population average atlases did not result in better predictions compared to random atlases. PCA-based representation did not clearly outperform other representations, although summary metrics indicated that PCA-based representations performed somewhat better in our sample. Representations with more regions or components resulted in less accurate predictions. Population average atlases possibly cannot distinguish between functionally distinct areas when applied to patients with a glioma. This stresses the need to develop and validate methods for individual parcellations in the presence of lesions. Future studies may test if the observed small advantage of PCA-based representations generalizes to other data.

Modelling of the catalytic initiation of methane coupling under non-oxidative conditions - R.S. Postma; P.S.F. Mendes; L. Pirro; A. Banerjee; J.W. Thybaut; L. Lefferts (Chemical Engineering Journal, 2023)

Innovating transcriptomics for practitioners in freshwater fish management and conservation: best practices across diverse resource-sector users - C. A. D. Semeniuk; K. M. Jeffries; T. Li; C. M. Bettles; S. J. Cooke; B. A. Dufour; E. A. Halfyard; J. W. Heath; K. Keeshig; N. E. Mandrak; A. J. Muir; L. Postma; et al. (Reviews in Fish Biology and Fisheries, 2022)

Plant density modifies root system architecture in spring barley (Hordeum vulgare L.) through a change in nodal root number - V. L. Hecht; V. M. Temperton; K. A. Nagel; U. Rascher; R. Pude; Johannes A. Postma (Plant and Soil, 2019)

Solubility Constraints on Aquatic Ecotoxicity Testing of Anionic Surfactants - J. Hammer; A. M. Tukker; J. F. Postma; J. J. -H. Haftka; J. L. M. Hermens; P. de Voogt; M. H. S. Kraak (Bulletin of Environmental Contamination and Toxicology, 2018)

Shared and distinct anatomical correlates of semantic and phonemic fluency revealed by lesion-symptom mapping in patients with ischemic stroke - J. Matthijs Biesbroek; Martine J. E. van Zandvoort; L. Jaap Kappelle; Birgitta K. Velthuis; Geert Jan Biessels; Albert Postma (Brain Structure and Function, 2016)

Modelling root–soil interactions using three–dimensional models of root growth, architecture and function - Vanessa M. Dunbabin; Johannes A. Postma; Andrea Schnepf; Loïc Pagès; Mathieu Javaux; Lianhai Wu; Daniel Leitner; Ying L. Chen; Zed Rengel; Art J. Diggle (Plant and Soil, 2013)

Modelling root plasticity and response of narrow-leafed lupin to heterogeneous phosphorus supply - Ying L. Chen; Vanessa M. Dunbabin; Johannes A. Postma; Art J. Diggle; Kadambot H. M. Siddique; Zed Rengel (Plant and Soil, 2013)

Superior spatial touch: improved haptic orientation processing in deaf individuals - Rick van Dijk; Astrid M. L. Kappers; Albert Postma (Experimental Brain Research, 2013)

Prevalence of antibodies against Ascaris suum and its association with allergic manifestations in 4-year-old children in the Netherlands: the PIAMA birth cohort study - E. Pinelli; S. M. Willers; D. Hoek; H. A. Smit; L. M. Kortbeek; M. Hoekstra; J. Jongste; F. Knapen; D. Postma; M. Kerkhof; R. Aalberse; J. W. B. Giessen; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

Differential effects of non-informative vision and visual interference on haptic spatial processing - Robert Volcic; Joram J. van Rheede; Albert Postma; Astrid M. L. Kappers (Experimental Brain Research, 2008)

Keep an eye on your hands: on the role of visual mechanisms in processing of haptic space - Albert Postma; Sander Zuidhoek; Matthijs L. Noordzij; Astrid M. L. Kappers (Cognitive Processing, 2008)

Haptic spatial orientation processing and working memory - Albert Postma; Sander Zuidhoek; Astrid M. L. Kappers; Matthijs L. Noordzij (Cognitive Processing, 2006)

DISSOLVING STOCK DISCRETENESS WITH SATELLITE TRACKING: BOWHEAD WHALES IN BAFFIN BAY - M. P. Heide‐JØrgensen; K. L. Laidre; M. V. Jensen; L. Dueck; L. D. Postma (Marine Mammal Science, 2006)
Nine bowhead whales ( Balaena mysticetus ) were instrumented with satellite transmitters in West Greenland in May 2002 and 2003. Transmitters were either encased in steel cans or imbedded in floats attached to wires. Transmitters mounted in steel cans had a high initial failure rate, yet those that were successful provided tracking durations up to seven months. Float tags had a low initial failure rate and initially provided large numbers of positions; however, they had deployment durations of only 2–33 d. All tracked whales departed from West Greenland and headed northwest towards Lancaster Sound in the end of May. Three tags with long tracking durations (197–217 d) recorded movements of whales (1 ♂, 2 ♀) into December in 2002 and 2003. All of these individuals remained within the Canadian High Arctic or along the east coast of Baffin Island in summer and early fall. By the end of October, all three whales moved rapidly south along the east coast of Baffin Island and entered Hudson Strait, an apparent wintering ground for the population. One of the whales did not visit Isabella Bay on east Baffin Island, the locality used for abundance estimation from photographic reidentification of individuals. The movements of whales tagged in this study raise critical questions about the assumed stock discreteness of bowhead whales in Foxe Basin, Hudson Strait, and Davis Strait and indicate current estimates of abundance are negatively biased.

Within-trophic group interactions of bacterivorous nematode species and their effects on the bacterial community and nitrogen mineralization - M. B. Postma-Blaauw; F. T. de Vries; R. G. M. de Goede; J. Bloem; J. H. Faber; L. Brussaard (Oecologia, 2005)

Improved neuromonitoring during spinal surgery using double-train transcranial electrical stimulation - H. L. Journée; H. E. Polak; M. de Kleuver; D. D. Langeloo; A. A. Postma (Medical & Biological Engineering & Computing, 2004)

Delay improves performance on a haptic spatial matching task - Sander Zuidhoek; Astrid M. L. Kappers; Rob H. J. van der Lubbe; Albert Postma (Experimental Brain Research, 2003)

Morphological Deformities in Chironomus Riparius Meigen Larvae after Exposure to Cadmium over Several Generations - L. Janssens de Bisthoven; J. Postma; A. Vermeulen; G. Goemans; F. Ollevier (Water, Air, & Soil Pollution, 2001)

Abstracts of presentations at the 22nd Congress of the Israeli Phytopathological Society February 12–13,2001 ARO, The Volcani Center, Bet Dagan, Israel - D. Shtienberg; M. Reuveni; N. Shegalov; D. Shegalov; D. Eshel; Ruth Ben-Arie; D. Prusky; Nadia Korolev; J. Katan; Talma Katan; A. Sharon; L. Oren; et al. (Phytoparasitica, 2001)

Spatial localization in patients with unilateral posterior left or right hemisphere lesions - A. Postma; Y. Sterken; L. de Vries; E.H.F. de Haan (Experimental Brain Research, 2000)

Fluctuating Life-History Parameters Indicating Temporal Variability in Metal Adaptation in Riverine Chironomids - D. Groenendijk; B. van Opzeeland; L. M. Dionisio Pires; J. F. Postma (Archives of Environmental Contamination and Toxicology, 1999)

Quantitative aspects of glucose metabolism by Escherichia coli B/r, grown in the presence of pyrroloquinoline quinone - R. W. J. Hommes; J. A. Simons; J. L. Snoep; P. W. Postma; D. W. Tempest; O. M. Neijssel (Antonie van Leeuwenhoek, 1991)

Virulence of Escherichia coli in acute pyelonephritis, acute cystitis and asymptomatic bacteriuria - J. F. van den Bosch; P. L. Oe; P. Postma; J. de Graaff; D. M. MacLaren; W. H. Jansen; P. A. M. Guinée (Antonie van Leeuwenhoek, 1980)